From the Information Society to the Knowledge Society: Towards a Conceptual Approach. - tallah, lamia (Journal of Social Sciences and Humanities, 2021)
The great cognitive revolution we are witnessing today, due to the large increase in the amount of published sources of explicit information, to the extent that the latest statistics indicate that the information will double every 73 days by 2020, and the ensuing repercussions, such as increasing the need to activate the role of Ras Knowledge in economic and social development, the rapid development of information technologies and the use of the Internet, the spread of globalization, and the subsequent increase in intellectual and human exchange, the development of information communication methods, as well as the tendency of the economy to adopt information as a basic resource, no less important than the material resource, or what The so-called knowledge economy, all this has led to the emergence of the so-called information society, which depends in its entirety on the acquisition and use of information and knowledge.